Design and Synthesis of 7-(N-Aryl Pyrrolidinyl) Indoles as Potential DCAF15 Binders - Ravi Devarajappa; Scarlett Kiyeleko; Sofiane Hocine; Victor Cosson; Remi Calandrino; Timea Baló; Jayson Alves Bordelo; Sébastien Triboulet; Laure Caruana; Laurence Klipfel; Sandrine Calis; András Herner; et al. (Reactions)
We describe the design and synthesis of a series of 7-(N-aryl pyrrolidinyl) indoles and oxo-analogs as isosteric mimics of the DCAF15 binder E7820, a well-known member of aryl sulfonamides known as SPLAMs. The functionalization of C-7 in indoles was achieved by metal-catalyzed CH-activation with unexpected results. Binding assays revealed the pyrrolidine N-aryl carboxylic acid analog to be as equally active as E7820.